Μουσείο οίνου και οινοποιητική μονάδα στις Αρχάνες Κρήτης - Σαββάκη, Άννα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών. Τομέας Αρχιτεκτονικής Γλώσσας, Επικοινωνίας και Σχεδιασμού, 2017)
The diploma thesis concerns the construction of a wine museum and a winery in Archanes, Crete. The winery is part of the wine road of Crete, consisting of 19 small winemaking units. The aim of the thesis is to enhance wine tourism, production as well as to promote the history and tradition of the region.